2021
DOI: 10.3390/app12010398
|View full text |Cite
|
Sign up to set email alerts
|

Effective and Low-Maintenance IMTA System as Effluent Treatment Unit for Promoting Sustainability in Coastal Aquaculture

Abstract: Integrated multitrophic aquaculture (IMTA) is a versatile technology emerging as an ecological and sustainable solution for traditional monoculture aquacultures in terms of effluent treatment. Nevertheless, IMTA is still poorly applied in aquaculture industry due to, among other reasons, the lack of effective, low-investment and low-maintenance solutions. In this study, one has developed a practical and low maintenance IMTA-pilot system, settled in a semi-intensive coastal aquaculture. The optimisation and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The high specific growth values observed by Resende et al [36] in an autumn experiment are lower compared to the same experiment conducted in the spring months (specific growth rate of 14.48 ± 3.52% d −1 ) with temperatures ranging from 19.57 to 28.5 • C and at 26.3 salinity. Culture temperature can be a key factor in macroalgae growth.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The high specific growth values observed by Resende et al [36] in an autumn experiment are lower compared to the same experiment conducted in the spring months (specific growth rate of 14.48 ± 3.52% d −1 ) with temperatures ranging from 19.57 to 28.5 • C and at 26.3 salinity. Culture temperature can be a key factor in macroalgae growth.…”
Section: Discussioncontrasting
confidence: 68%
“…Despite the increase in biomass in this experiment in an integrated biofloc system, Resende et al [36] showed a maximum specific growth rate of 3.91 ± 0.67% d −1 of the macroalgae Ulva spp. in integrated culture with clear water, during autumn with temperatures ranging from 9.6 to 14.9 • C. This shows that the biofloc system can interfere with the performance of the macroalgae, and that better management procedures can be adopted.…”
Section: Discussioncontrasting
confidence: 54%
“…Despite the lower concentration of solids in the chemoautotrophic system, they still accumulated on the surface of the macroalgae, representing one of the challenges of biofloc systems. Studies like Resende et al [6] reported significantly higher growth rates, with a maximum growth rate of 15.33 ± 2.87% day −1 when macroalgae were cultivated freely in tanks with fish farm effluent, characterized by minimal solids concentrations. The results found in our experiment are in agreement with studies by Martins et al [52], who observed a growth rate of 3.0 ± 0.6% day −1 with the macroalga Ulva ohnoi in a biofloc system.…”
Section: Discussionmentioning
confidence: 97%
“…The cultivation of macroalgae integrated with other aquatic organisms has gained traction in aquaculture, referred to as Integrated Multitrophic Aquaculture (IMTA) [5]. Resende et al [6] demonstrated the feasibility of incorporating macroalgae for nutrient absorption and biomass production in open cultivation systems with Sea bream Sparus aurata and European sea bass Dicentrarchus labrax. In addition to macroalgae serving as inorganic consumers, the IMTA system also includes organic consumers to consume the solids produced in the system.…”
Section: Introductionmentioning
confidence: 99%
“…A microbial oxidative process transforms toxic metabolites such as NH 3 + or NO 2 − into chemical forms less toxic (ammonium or nitrate) to culture organisms through the intervention of nitrifying bacteria [46]. Biofiltration of aquaculture waste consists of substrate and plant systems used for filtration, reduction, and removal of suspended solids [47] macro and micronutrients [48] as well as heavy metals [49]. Where the removal of these components depends on a complex interaction of physical, chemical, biological processes (sedimentation, adsorption, coprecipitation, cation exchange, photodegradation, phytoaccumulation, biodegradation, and microbial activity) and mainly on the type of plant used, as well as its absorption rate [50] in each retention time [51].…”
Section: Biofiltration Of Aquaculture Wastementioning
confidence: 99%